Design, synthesis, and antiviral evaluation of novel hydrazone‐substituted thiophene[3, 2‐d]pyrimidine derivatives as potent human immunodeficiency virus‐1 inhibitors. (26th August 2018) - Wang, Zhao; Kang, Dongwei; Chen, Meng; Wu, Gaochan; Feng, Da; Zhao, Tong; Zhou, Zhongxia; Huo, Zhipeng; Jing, Lanlan; Zuo, Xiaofang; Daelemans, Dirk; De Clercq, Erik; et al.
Abstract: In the previous studies of our laboratory, the thiophene[3, 2‐ d ]pyrimidine was identified as a promising scaffold for seeking highly potent HIV‐1 non‐nucleoside reverse transcriptase inhibitors (NNRTIs). In this study, we designed, synthesized, and biologically evaluated a series of thiophene[3, 2‐ d ]pyrimidine derivatives with changed linker between the thiophenepyrimidine core and the right wing. Some of the synthesized compounds exhibited excellent HIV‐1 inhibitory potency with low (double‐digit) nanomolar 50% effective concentration (EC50 ) values. Among them, compound13a exhibited the most potent anti‐HIV‐1 activity (EC50  = 21.2 nM), which was 10‐fold greater than that of NVP (EC50  = 281 nM). Moreover, 13a showed much lower cytotoxicity (CC50  = 183 μM) and higher selection index (SI = 8, 632) than NVP, ETV, and AZT. Besides, some physicochemical properties and water solubility were calculated or measured. The preliminary structure–activity relationships and molecular simulation studies of these compounds were also discussed comprehensively to provide valuable direction for further design and optimization. Abstract : In the present study, we designed, synthesized, and biologically evaluated a series of thiophene[3, 2‐ d ]pyrimidine derivatives bearing the hydrazone linker between the thiophenepyrimidine core and the right wing. In particular, compound13a exhibited the most potent anti‐HIV‐1 activity. Besides, some physicochemical properties and water solubility were calculated or measured. The preliminary structure–activity relationships and molecular simulation studies of these compounds were also discussed comprehensively to provide valuable direction for further design and optimization.